(x+8×2+6×8)-8×9+8×8=6×10+2×4
Răspunsuri la întrebare
Răspuns de
6
(x+8x2+6x8)-8x9+8x8=6x10+2x4
(x+16+48)-8x9+8x8=6x10+2x4
(x+64)-8x9+8x8=6x10+2x4
(x+64)-72+64=60+8
(x+64)-72+64=68
(x+64)-72=68-64
(x+64)-72=4
(x+64)=72+4
x+64=76
x=76-64
x=12
(x+16+48)-8x9+8x8=6x10+2x4
(x+64)-8x9+8x8=6x10+2x4
(x+64)-72+64=60+8
(x+64)-72+64=68
(x+64)-72=68-64
(x+64)-72=4
(x+64)=72+4
x+64=76
x=76-64
x=12
Răspuns de
3
(x + 8×2 +6×8 ) - 8×9 + 8 × 8 =6×10+2×4
(x + 16 + 48) - 72 + 64 = 60 + 8
(x + 64) - 72 + 64 = 68
x + 64 = 68 - 64 + 72 → metoda mersului invers
x + 64 = 4 + 72
x + 64 = 76
x = 76 - 64
x = 12
(x + 16 + 48) - 72 + 64 = 60 + 8
(x + 64) - 72 + 64 = 68
x + 64 = 68 - 64 + 72 → metoda mersului invers
x + 64 = 4 + 72
x + 64 = 76
x = 76 - 64
x = 12
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Chimie,
9 ani în urmă
Limba rusă,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă